A CONCEPTUAL MODEL OF TRI HITA KARANA IN EDUCATIONAL GLOCALIZATION: TOWARD ETHICAL CULTURAL COMMODIFICATION - L. Virginayoga Hignasari; Made Sutajaya; Md. Yudyantara Risadi; Putu Putri Dena Laksmi; I Wayan Budiarta; Yuni Misrahayu; Noor Akhmad; Agustinasari; Ni Komang Dwi Eka Yuliati (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
This study examines the repositioning of Tri Hita Karana (THK) within the context of educational glocalization in Bali. Previous studies have predominantly treated THK as a normative and ceremonial value system, with limited attention to its potential as a strategic epistemic and educational framework. Using a qualitative conceptual approach based on documentary analysis and a critical interpretive perspective, this study aims to develop a conceptual model of THK implementation in educational glocalization and to explore how ethical cultural commodification may function as a strategy for cultural empowerment rather than mere commercialization. The study develops a three layer conceptual model consisting of: (1) a value foundation layer that positions THK as the ontological and epistemic basis of education; (2) an educational transformation layer that conceptualizes glocalization as a mechanism for integrating local values into curriculum, pedagogy, and cross-cultural learning processes; and (3) an empowerment and cultural bargaining layer that frames education as a space for cultural diplomacy, community collaboration, and ethically grounded cultural commodification. These layers are operationalized into six strategic phases, including institutional legitimation, value internalization, cross-cultural negotiation, curriculum glocalization, cultural dissemination, and value-based commodification. The findings indicate that THK can function not only as a framework for cultural preservation but also as strategic cultural capital capable of strengthening educational identity, cultural agency, and local-global negotiation within contemporary education. The study contributes a conceptual framework that repositions THK from a symbolic cultural philosophy into a dynamic educational model relevant to multicultural and globalized learning environments.